Aspectos ecológicos de la anidación de Caiman crocodilus chiapasius (Bocourt, 1876) en la reserva de la biosfera La Encrucijada, México - González–Desales, G. A.; Monroy–Vilchis, O.; Charruau, P.; Zarco–González, M. M. (Animal Biodiversity and Conservation, 2016)
Ecological aspects of nesting in Caiman crocodilus chiapasius (Bocourt 1876) in La Encrucijada Biosphere Reserve, Mexico Studies on caiman, Caiman crocodilus chiapasius, in Mexico are scarce. The present study was conducted to evaluate the key characteristics regarding the reproductive ecology of caiman in Mexico. We conducted nest searches from April to September 2014. We observed that nests were built in June and that hatching occurred in September and October. The phase of the moon had an effect on nesting events. The height of the nest, the distance to the nearest tree, and the distance from the top of the nest to the first egg were related to hatching success and incubation temperature.